2021
DOI: 10.1002/open.202000258
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low Vapor‐Pressure Data as Access to PC‐SAFT Parameter Estimation for Ionic Liquids and Modeling of Precursor Solubility in Ionic Liquids

Abstract: Precursor solubility is a crucial factor in industrial applications, dominating the outcome of reactions and purification steps. The outcome and success of thermodynamic modelling of this industrially important property with equations of states, such as Perturbed‐Chain Statistical Associating Fluid Theory (PC‐SAFT), vastly depends on the quality of the pure‐component parameters. The pure‐component parameters for low‐volatile compounds such as ionic liquids (ILs) have been commonly estimated using mixture prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…For the presently investigated ionic liquids, it varies from 136 ± 18 kJ/mol for m-C 6 H 4 (CH 2 ImMe)][NTf 2 ] 2 to 147 ± 12 and 147 ± 13 kJ/mol for [DABCO10][NTf 2 ] and [p-C 6 H 4 (CH 2 ImBu)][NTf 2 ] 2 , respectively, and finally to 180 ± 17 kJ/mol for [C 6 Py][NTf 2 ]. These values are consistent with those previously reported for the other ionic liquids [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For the presently investigated ionic liquids, it varies from 136 ± 18 kJ/mol for m-C 6 H 4 (CH 2 ImMe)][NTf 2 ] 2 to 147 ± 12 and 147 ± 13 kJ/mol for [DABCO10][NTf 2 ] and [p-C 6 H 4 (CH 2 ImBu)][NTf 2 ] 2 , respectively, and finally to 180 ± 17 kJ/mol for [C 6 Py][NTf 2 ]. These values are consistent with those previously reported for the other ionic liquids [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultssupporting
confidence: 93%
“…ILs containing the B(CN) 4 anion have p v comparable to that of NTf 2 samples [ 31 ]. Bulow et al reported a comparison of the vapor pressure of ILs containing the same 1-ethyl-3-methyl-imidazolium cation and a series of anions, such as PF 6 , B(CN) 4 , (C 2 H 5 O) 2 PO 2 , NTf 2 , SCN, CF 3 CO 2 , CF 3 SO 3 , BF 4 , C(CN) 3 , (C 2 F 5 ) 3 PF 3 , 4-CH 3 -Ph-SO 3 [ 32 ]. Finally, in the last couple of years some models were also proposed to derive the vapor pressure and vaporization enthalpy values from the knowledge of the structure of ILs [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…One which accounts for the ionic character and utilizes ion-specific parameters, and one that, similar to conventional solvents, is based on a molecular parameterization. In a recent publication, the molecular and ion-specific approaches have been compared with emphasis on the prediction of sour-gas absorption into the pure IL . Although utilizing the extremely low vapor pressure of the IL in the parameter estimation in the molecular approach, the ion-specific parameter set was superior at higher pressures.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In a recent publication, the molecular and ion-specific approaches have been compared with emphasis on the prediction of sour-gas absorption into the pure IL. 44 Although utilizing the extremely low vapor pressure of the IL in the parameter estimation in the molecular approach, the ion-specific parameter set was superior at higher pressures. Therefore, an ion-specific approach is also chosen here to model the IL.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…47 The remaining molecular parameters (i.e., m, σ, ε) were obtained from fitting to available liquid density data, which is acceptable considering the low vapor pressure of ILs, and the reduced degree of freedom during parametrization from fixing the association parameters a priori. 56,57 The diluents were also modeled taking into account their governing intermolecular interactions. The dipolar diluents acetone and NMP were modeled with explicit consideration of their dipolar nature.…”
Section: The Polar Soft-saft Equation Of State (Eos)mentioning
confidence: 99%